2018
DOI: 10.1101/335042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional recognition training modifies neural response to emotional faces but does not improve mood in healthy volunteers with high levels of depressive symptoms

Abstract: IMPORTANCEDepression is a debilitating and highly prevalent mental health disorder. There is a need for new, effective, and scalable treatments for depression, and cognitive bias modification (CBM) of negative emotional processing biases has been suggested as one possibility. Such treatments may form the basis of 'digital therapeutics', that could be administered remotely and at low cost, should they prove to be effective. OBJECTIVESStudy one was designed to determine neural correlates of a recently developed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Indeed, packages of emotion recognition training are being developed to address this issue (e.g. the study by Penton-Voak et al 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, packages of emotion recognition training are being developed to address this issue (e.g. the study by Penton-Voak et al 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…And, dominance expressions facilitate recognition of anger (Montepare & Dobish, 2003). Conversely, feminine features, such as large eyes and round faces, are associated with neonates and lead to judgments of submissiveness (e.g., Le Gal & Bruce, 2002; Penton-Voak, Wisbey, & Pound, 2007; Zebrowitz & Montepare, 2015). Indeed, lowering one’s brow and narrowing one’s eyes can be used to signal anger.…”
Section: Target Characteristics Influence the Interpretation Of Expre...mentioning
confidence: 99%
“…However, in a recent study investigating the effect of WM training, Jopling et al (2020) did not find any training‐related improvements in depressive symptoms or rumination in patients with depression. Empirical studies investigating the effects of WM training in dysphoria have been infrequent, and the cognitive and neural mechanism underlying the remediating effect on depressive symptoms is less investigated (Owens et al, 2013; Penton‐Voak et al, 2020). In healthy volunteers, it has been found that multiple‐session training targeting interference control of neutral distractors could increase one's ability to resist negative distractors, and the training reduced amygdala reactivity to negative distractors (Cohen et al, 2016); thus, interference control training holds great potentials for alleviating depressive symptoms in sub‐clinical and clinical samples.…”
Section: Discussionmentioning
confidence: 99%